Market Analysis of Zoological Products: Trends and Ethical Considerations - Pandian, S. Kulothunga; Gandhi, M. Rajeev; Malainambirajan, T. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The market for zoological products, including items such as leather, ivory, exotic pets, and traditional medicines, has undergone significant growth and transformation over recent decades. This paper aims to provide a comprehensive market analysis of zoological products, focusing on current trends and ethical considerations. Utilizing both primary data from surveys of 200 consumers and 50 retailers, and secondary data from academic journals, industry reports, and official statistics, the study examines market size, consumer behavior, regulatory frameworks, and ethical dilemmas. The findings highlight the economic importance of zoological products while emphasizing the need for sustainable and ethical practices to ensure wildlife conservation. This research contributes to the discourse on balancing commercial interests with ethical considerations, offering insights for policymakers, retailers, and consumers. Future research should explore the impact of emerging regulations and the effectiveness of consumer education programs in promoting ethical consumption.